Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/acs.analchem.5b01035
|View full text |Cite
|
Sign up to set email alerts
|

Nanopillar Based Enhanced-Fluorescence Detection of Surface-Immobilized Beryllium

Abstract: The unique properties associated with beryllium metal ensures the continued use in many industries despite the documented health and environmental risks. While engineered safeguards and personal protective equipment can reduce risks associated with working with the metal, it has been mandated by the Environmental Protection Agency (EPA) and Occupational Safety and Health Administration (OSHA) that the workplace air and surfaces must be monitored for toxic levels. While many methods have been developed to monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…To meet these high demands, we decided to use a platform that may compromise some of the optimized enhancement for quickly fabricated vast pillar array substrates, namely, stochastic platinum DW pillar arrays, whose usefulness has been previously expounded upon. 6 , 24 , 25 To create these arrays, we first needed to determine the optimum pillar diameter range.…”
Section: Methodsmentioning
confidence: 99%
“…To meet these high demands, we decided to use a platform that may compromise some of the optimized enhancement for quickly fabricated vast pillar array substrates, namely, stochastic platinum DW pillar arrays, whose usefulness has been previously expounded upon. 6 , 24 , 25 To create these arrays, we first needed to determine the optimum pillar diameter range.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the excellent properties of nanopillar structures, Charlton et al . developed optical field-enhanced silicon nanopillars for the detection of DNA [ 27 ]. Lee et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nanopillar structures can be fabricated by nanoimprint lithography, a two-dimensional nanostructure manufacturing technique that enables simple, low-cost, and high-throughput production [22][23][24][25][26]. Based on the excellent properties of nanopillar structures, Charlton et al developed optical field-enhanced silicon nanopillars for the detection of DNA [27]. Lee et al reported a localized surface plasmon resonance nanopillar biosensor prepared by nanoimprint lithography [28].…”
Section: Introductionmentioning
confidence: 99%
“…throneas as chelating agents and extraction by using micelle and mixed micelles-based cloud point extraction (7,(10)(11)(12)(13). Recently, hydroxybenzoquinoline fluorescent chelating agents immobilized in a silica nanopiller platform and silica gel-loaded column have been used for extraction of beryllium (14,15). Nevertheless, these are time-consuming methods, and routine analysis is not possible.…”
Section: Introductionmentioning
confidence: 99%